Study on Academic Anxiety and Academic Achievement Among Science and Arts Stream Students at the Higher Secondary Level - Nayak, Chakradhar; Barik, Debasish (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The present study aimed to examine the levels of academic anxiety and academic achievement among science and arts stream students of higher secondary level. The objectives of the study were to access the academic anxiety and academic achievement and to examine the relationship between these two factors among students. The study involved a sample of 200 students comprising 100 from science and 100 from arts stream selected from four higher secondary schools in Baripada subdivision of Mayurbhanj district, Odisha. The “Academic Anxiety Scale for Children” by A.K. Singh and Dr. A. Sen Gupta was used as tool for data collection and students’ previous examination scores were used to assess students' academic performance in both Science and Arts streams. The schools were chosen using purposive sampling while, simple random sampling was used for selecting students. The findings of the study revealed that students in science stream experienced significantly higher levels of academic anxiety compared to Arts stream students. In terms of academic achievement, Science students also performed significantly better than Arts students. But there was a statistically significant negative correlation was found between academic anxiety and academic achievement, suggesting that higher anxiety levels were associated with lower academic performance.